Shared biosynthesis of the saliniketals and rifamycins in Salinispora arenicola is controlled by the sare1259 encoded cytochrome P450 - Wilson, Micheal C. (2010)
Saliniketals A and B are unusual polyketides from the marine actinomycete Salinispora arenicola that inhibit ornithine decarboxylase induction. The structural similarities between the saliniketals and the ansa chain of the potent rifamycin antibiotics, which co-occur in the fermentation broth, suggest a common origin between the two compound classes. Using PCR-directed mutagenesis, chemical complementation studies, and stable isotope feeding experiments, we showed that the saliniketals are byproducts of the rifamycin biosynthetic pathway diverging at the stage of 34a-deoxyrifamycin W. Our results suggest that a single enzyme, the cytochrome P450 monooxygenase encoded by sare1259, catalyzes multiple oxidative rearrangement reactions on 34a-deoxyrifamyin W to yield both the saliniketal and rifamycin structural classes.